MILTON SANTOS: PENSAMENTO GLOBAL E EDUCA??O - Silva, Renata Lopes da (2009)
The current research work, entitled ?Milton Santos: Global Thought and Education? presents a study on the intellectual Milton Santos (1926 ? 2001), a professor who intensely fuels the debate about elements which are part of the world reality and, especially the Brazilian one. The questioning that surrounded such study was based on the need of constant investigations about the historical complexity of present, the contradictory reality in which Education is inserted, as well as that Education might be understood and transformed into this social-historical context and take some posture which is contrary to the capital logic. We kept our research into the study of the concepts of ?Space?, ?Globalization?, `Globalitarism?, ?Only thought?, ?Universal Thought?, ?Citizenship? and ?Experience?, ?wisdom of lack? which represent some of the theoretical elements that match with professor Milton Santos?s thoughts, making a parallel with the formal contemporary Brazilian Education. Based on the theoretical methodological assumptions of the Marxist theory, we sought to locate the problematic in the macro-structural context, relating it to the particularities of the concepts studied, trying to make a parallel with the totality social classes struggle, contradiction and hegemony. The study about MILTON concepts provide analytical subsidies for the understanding of the social-historical contemporary context in which the policies for the formal Brazilian Education are and where discussions regarding its transformation are postulated. We tried to establish, according to the MILTON concept of intellectual, its relevancy for the organization and social mobilization, as well as its relation to Education. The research made by the intellectual Milton Santos shows the dimension of the fundaments of a new Geography, and although it is not a common reference in the Education field, the concepts made by him contribute to the comprehension of a real representation of the social context in which Education is inserted, and therefore, we considered the importance of the detailed examination about his thought. However, we do not intend to use up the discussions around Professor Milton Santos thoughts with this research, but only raise the knowledge and debate about part of the concepts present in his work for the real theoretical and practical coping turned to the debate on Education, History of Education, Education Policy, development and performance of intellectuals throughout history Brazil.